The Impact Of The Quality Of Electronic Banking Services On Customers Satisfaction In Bank of Commerce & Development In Benghazi Libya - Adel Al-Tawaty, Jeenan; Ahmed Al-Legmaty, Asma; Faraj Al-Arafi, Heba; Adam Al-Barghathy, Laila (Libyan International Medical university "Faculty of Information Technology", 2017)
This study conducted to measure the impact of quality of electronic banking services on customer satisfaction, and this study came to test hypothesis to solve the research problem. The population of this study was faculty members of Libyan International Medical University customers in Bank Of Commerce & Development in Benghazi Libya. To achieve the objectives of this study an E-SERVQUAL questionnaire model was used to collect data from the sample, the questionnaire was distributed to 40 person and 33 was returned. And SPSS software was used in the analysis. The results was. 1- The level of overall satisfaction was high for the target sample. 2- Mean score for the dimensions indicates that there is a slight increase in the level of satisfaction for each dimension. 3- The satisfaction does not influenced by customs’ age , gender, qualification , or faculty. 4- The banks must conduct a periodic studies to measure the effectiveness of electronic banking services to maintain the customers.